Pengembangan dan Validasi Sistem Pemantauan Mikroklimat Real-Time Berbasis IoT sebagai Pendukung Evaluasi Kondisi Pengeringan Pascapanen pada Solar Dome Dryer - Joko Riyanto; Anton Yudhana; Abdul Fadlil (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Continuous monitoring of temperature and humidity is necessary to evaluate the microclimate conditions that affect the drying performance of agricultural products in the Solar Dome Dryer. However, manual monitoring has not been able to provide real-time data, while previous research has largely focused on the implementation of devices without validating the measurements against standard measuring instruments under operational drying conditions. This research aims to develop a real-time microclimate monitoring system based on the Internet of Things to support the evaluation of post-harvest drying performance on the Solar Dome Dryer. The system was developed using the DHT22 sensor, ESP32 microcontroller, Wi-Fi connection, and cloud platform to display temperature and humidity data through a web-based and smartphone dashboard. Testing was conducted on the functions of acquisition, transmission, data visualisation, and sensor accuracy by comparing the measurement results with the standard measuring instrument UNI-T UT333. During the testing, the system was able to record and transmit microclimate data stably within the temperature range of 29.1–65.6 °C and relative humidity of 13.7–79.5% RH. In a limited test of 100 transmission cycles with a 10-minute interval, all data were successfully received by the server under network conditions during the testing. Validation using 50 pairs of data resulted in an MAE of 0.150 °C and an RMSE of 0.159 °C for temperature, as well as an MAE of 0.286% RH and an RMSE of 0.293% RH for humidity. The MAPE values were 0.34% and 0.92%, respectively. The contribution of this research is the development of a low-cost microclimate monitoring framework that integrates acquisition, transmission, storage, real-time visualisation, and statistical sensor validation under the operational conditions of the Solar Dome Dryer. The system can be used as a data source to support drying condition evaluations, with the limitation that accuracy validation above 60 °C has not yet been conducted using appropriate reference instruments.